The Gradient of a Solution of the Poisson Equation in the Unit Ball and Related Operators. Issue 3 (1st September 2017) - Kalaj, David; Vujadinovic, Djordjije
Abstract: In this paper we determine the ${L^{1}}→ {L^{1}}$ and ${L^{∞ }}→ {L^{∞ }}$ norms of an integral operator $\mathcal{N}$ related to the gradient of the solution of Poisson equation in the unit ball with vanishing boundary data in sense of distributions.